EVALUASI PEMANFAATAN MEDIA ELEKTRONIK BAGIAN HUMAS DAN PROTOKOL PADA SEKRETARIAT DAERAH KABUPATEN SUMBA BARAT - Pelina Ida Moi Here; Laurensius P. Sayrani; Aminudin Zuhairi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to evaluate the use of electronic media by the Public Relations and Protocol Section at the Regional Secretariat of West Sumba Regency and the inhibiting factors for the use of electronic media by the Public Relations and Protocol Section at the Regional Secretariat of West Sumba Regency. This research is research with qualitative type. Informants as data sources in this study were the head of local government public relations, public relations staff, management of electronic media owners, and community members. This research instrument includes documentation, observation, and interview instruments. Data were analyzed with qualitative methods. Based on the results of the research analysis it is known that the Evaluation of Utilization of Electronic Media (Public Relations and Protocol of West Sumba Regency) refers to the indicators of Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness and Accuracy can be categorized as quite good, it is known that Public Relations and Protocol of West Sumba Regency have made use of electronic media with costs that are in accordance with the results and benefits received, able to provide benefits to society and the government, able to reach all segments without exception, and in accordance with the objectives. Obstacles in Utilization of Electronic Media Public Relations and West Sumba Regency Protocol) include a lack of human resources, lack of HR technical skills, no routine monitoring activities, not yet working with journalists, and no evaluation activities on the achievement of the development of West Sumba Regency Public Relations and Protocol.